The Functional Movement Screen as a predictor of injury in National Collegiate Athletic Association Division II athletes - Dorrel, B.; Long, T.; Shaffer, S.; Myer, G. D. (Journal of Athletic Training, 2018)
Context: The Functional Movement Screen (FMS) is a tool used to assess the quality of human movement. Previous FMS researchers reported a difference between the comprehensive and individual FMS test scores of injured and uninjured participants.